Steroid Drug Dangers - Monroe, Judy (Springfield, NJ : Enslow Publishers, 1999)
Discusses the short-term and long-term effects and dangers of steroid drug use, recounts the stories of various people who have abused them, and explains how to get help with this problem.
Includes bibliographical references and index.
Keywords: Anabolic steroids -- Health aspects; Doping in sports -- Juvenile literature; Steroids; Athletes -- Drug use; Drug abuse